A shared mechanism of defense against predators and parasites: chitin regulation and its implications for life‐history theory. Issue 15 (20th November 2013) - Beckerman, Andrew P.; de Roij, Job; Dennis, Stuart R.; Little, Tom J.
Abstract: Defenses against predators and parasites offer excellent illustrations of adaptive phenotypic plasticity. Despite vast knowledge about such induced defenses, they have been studied largely in isolation, which is surprising, given that predation and parasitism are ubiquitous and act simultaneously in the wild. This raises the possibility that victims must trade‐off responses to predation versus parasitism. Here, we propose that arthropod responses to predators and parasites will commonly be based on the endocrine regulation of chitin synthesis and degradation. The proposal is compelling because many inducible defenses are centered on temporal or spatial modifications of chitin‐rich structures. Moreover, we show how the chitin synthesis pathway ends in a split to carapace or gut chitin, and how this form of molecular regulation can be incorporated into theory on life‐history trade‐offs, specifically the Y‐model. Our hypothesis thus spans several biological scales to address advice from Stearns that "Endocrine mechanisms may prove to be only the tip of an iceberg of physiological mechanisms that modulate the expression of genetic covariance" . Abstract : All organisms deal with multiple forms of stress. Here we offer a physiological hypothesis explaining how many organisms might trade‐off a response to parasites and predators, two of the most important forms of stress and the ecological context for understanding one of the most important and common forms of phenotypic plasticity – inducible defences. Our hypothesis centers on chitin, one of the most abundant polysaccharides in nature, and we develop the compelling and testable hypothesis that by understanding the molecular and phyiological regulation of chitin synthesis and degradation we can reveal the mechanistic basis of trade‐offs against predators and parasites and understand better the evolution of complex traits in complex environments.